THE CULTURAL DIMENSIONS OF THE COVID-19 PANDEMIC IN THE CITY OF BISTRITA (ROMANIA) - Bîca, Ioan (REVISTA GEOGRÁFICA ACADÊMICA, 2022)
Disasters are unexpected events, triggered by natural or anthropogenic means, which cause material damage and human casualties. In addition to the technical, social, and economic dimensions, disasters also have cultural connotations, related to their perception, understanding, and acceptance by the community, the behavior of communities during the disaster, and the efforts made to return to normalcy. This is also the case with the Covid-19 pandemic, a biological disaster that triggered many reactions from the population about the origin of the new coronavirus, the meaning of the pandemic, the restrictions imposed by the authorities, the incoherence of the authorities in making decisions, the lack of medicines in hospitals, and pharmacies, about the treatment in hospitals, the reporting of infections, and deaths by health authorities, the content of the vaccine and the meaning of vaccination, etc. These cultural connotations can be traced in the present study, which was developed based on long observations made in the city of Bistrita in Romania.